Celiac disease from a global perspective. Issue 3 (June 2015) - Lionetti, Elena; Gatti, Simona; Pulvirenti, Alfredo; Catassi, Carlo
Abstract Celiac disease (CD) is one of the commonest lifelong disorders in countries populated by individuals of European origin, affecting approximately 1% of the general population. This is a common disease also in North Africa, Middle East and India. The widespread diffusion of CD is not surprising given that its causal factors (HLA predisposing genotypes and consumption of gluten-containing cereals) show a worldwide distribution. Further studies are needed to quantify the incidence of CD in apparently "celiac-free" areas such as Sub-Saharan Africa and Far East. Several reports have shown that CD is increasing in frequency in different geographic areas. Genetic factors do not explain the rising incidence during the last decades; environmental or lifestyle factors may be responsible for these changes over time. The majority of patients with CD are still undiagnosed all over the world, leading to debate about the need of screening program.